IDENTIFICATION AND REGISTER AMMONITES GENUS Raimondiceras Spath, 1924, FORMATION LA HERRADURA, MORRO SOLAR LOCATION, LIMA (VALANGINIAN) - Alleman Haeghebaert, Vera (2020)
Taxonomic collection of reference reposited in the Paleontology Department of the Natural History Museum“Vera Alleman Haeghebaert”of the Ricardo Palma University. It consists of the identification, register and the description of thirty-two specimens of the genus Raimondiceras Spath, 1924, of which twelve were attributed to the species Raimondiceras raimondii (Gabb, 1877), fifteen to the species Raimondiceraspflückeri (Lisson, 1904) and the remaining five to Raimondiceras sp. The initial taxonomic study was based on the original publications and fossils accessibles to the original authors; In addition, the identification key of the AMMONOIDEA species of the Morro Solar Group, Valanginian-Hauterivian of Lima, Peru (Alleman, 2014) was used.